2016
DOI: 10.1016/j.biochi.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The nutraceutical potential of omega-3 alpha-linolenic acid in reducing the consequences of stroke

Abstract: Stroke is a worldwide major cause of mortality and morbidity. Preclinical studies have identified over 1000 molecules with brain-protective properties. More than 200 clinical trials have evaluated neuroprotective candidates for ischemic stroke yet, to date almost all failed, leading to a re-analysis of treatment strategies against stroke. An emerging view is to seek combinatory therapy, or discovering molecules able to stimulate multiple protective and regenerative mechanisms. A pertinent experimental approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 61 publications
0
25
0
2
Order By: Relevance
“…omega-3 FA and conjugated linoleic acid), which are known to have many beneficial effects on human health (Biondi et al 2008;Renna et al 2012;Albenzio et al 2016). Omega-3 (n-3) fatty acids (FAs) are involved in the development of brain and retinal tissues and in the progression and prevention of human pathologies, including heart disease and some cancers (Blondeau 2016). Conjugated linoleic acid (CLA) has been reported to reduce the risk of cancer, cardiovascular diseases, diabetes, and obesity, as well as boosting the immune system (Wang & Lee 2015;Hennessy et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…omega-3 FA and conjugated linoleic acid), which are known to have many beneficial effects on human health (Biondi et al 2008;Renna et al 2012;Albenzio et al 2016). Omega-3 (n-3) fatty acids (FAs) are involved in the development of brain and retinal tissues and in the progression and prevention of human pathologies, including heart disease and some cancers (Blondeau 2016). Conjugated linoleic acid (CLA) has been reported to reduce the risk of cancer, cardiovascular diseases, diabetes, and obesity, as well as boosting the immune system (Wang & Lee 2015;Hennessy et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of ALA from a health perspective has been generally less reported relative to n-3 LC-PUFA, ALA is receiving interest as a nutraceutical supplement, based on reports of beneficial effects similar to those of n-3 LC-PUFA [44]. ALA is a minor fatty acid in marine oils, however, it is highly and naturally present in Camelina and other transgenic oilseeds such as canola, reaching proportions of over 25% of the total fatty acids in oils extracted from transgenic seed [18].…”
Section: Discussionmentioning
confidence: 99%
“…There was another study demonstrating that ALA provided a beneficial effect on the infarct size, neurological score, neuronal survival and mortality rate of ischemic mice in a clinically relevant model of stroke (Heurteaux et al, 2006). Recent review by Blondeau (2016) has presented the capacity of ALA for protecting the brain from stroke by direct neuroprotection, triggering brain artery vasodilatation and neuroplasticity to reduce the stroke damage. And in a mouse model of ischemic stroke, it was found that ALA intake would provide an enteral or parenteral nutritional intervention for sensorimotor and cognitive deficits (Bourouroua et al, 2016).…”
Section: Ala and Neurological Protectionmentioning
confidence: 99%